Optimal dietary approaches for prevention of type 2 diabetes: a life-course perspective - Buyken, Anette; Mitchell, P.; Ceriello, A.; Brand-Miller, J. (Diabetologia)

Urinary isoflavone phytoestrogens in German children and adolescents - A longitudinal examination in the DONALD cohort - Degen, Gisela H.; Blaszkewicz, Meinolf; Shi, Lijie; Buyken, Anette; Remer, Thomas (Molecular Nutrition & Food Research)

Explaining the Trading Venue Decision of Private Online Investors - An Empirical Study - Herrmann, Philipp; Kundisch, Dennis (International Workshop on Enterprise Applications, Markets and Services in the Finance Industry (FinanceCom))

Project interactions in value based IT project portfolio management - Meier, Christian; Kundisch, Dennis (Proceedings der GI-Jahrestagung Informatik 2010)

Sustainable Process Management - Status Quo and Perspectives - Kundisch, Dennis; Herrmann, Philipp; Meier, Christian (Proceedings of the 8th International Heinz Nixdorf Symposium (IHNS))

Mispricing and Exchange Market Systems: The Effect of Infrastructure Upgrades - Wagener, M.; Kundisch, Dennis; Riodan, R.; Rabhi, Fethi; Weinhardt, C. (Proceedings of the 43rd Hawaii International Conference on System Sciences (HICSS))

9. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung - Gausemeier, Jürgen; Grafe, M.

BiographIE - Biographical Information Extraction from Business News - Geierhos, Michaela; Blanc, Olivier (Actes du 27e Colloque international sur le lexique et la grammaire (L’Aquila, 10-13 septembre 2008))

BiographIE - Klassifikation und Extraktion karrierespezifischer Informationen - Geierhos, Michaela
Das wesentliche Ziel der vorliegenden Publikation ist die Erstellung von sprachspezifischen Modulen im Bereich der Biographischen InformationsExtraktion (BiographIE). Unter Informationsextraktion verstehen wir die automatisierte Analyse von Dokumenten im Hinblick auf das Entdecken und Normalisieren von semantisch interessanten Entitäten und deren Eigenschaften. Das Hauptgewicht der Arbeit liegt auf sehr detaillierten und umfangreichen linguistischen Grammatiken im Bereich der Beschreibung von Personen und deren Beziehungen zu anderen relevanten Entitäten (z.B. Organisationen, Orte, Datums- und Zeitangaben) in Texten. Neben den öffentlichen und privaten Eigenschaften von Personen (Geburtsdatum, Nationalität etc.) sollen vor allem alle biographisch relevanten Attribute aus Texten extrahiert werden können. Dazu gehören in erster Linie berufliche Werdegänge, Anstellungsverhältnisse, Rollen in Firmen und ähnliche Eigenschaften. Da alle diese Attribute in unzählbar verschiedenen Formen ausgedrückt werden können, müssen sehr umfangreiche Lexika und sehr detaillierte grammatische Beschreibungen erstellt werden. Dies geschieht hauptsächlich bei der systematischen Evaluierung von Korpora. Je umfangreicher diese sind, desto adäquater werden die erstellten Grammatiken sein. Im Gegensatz zu den heute üblichen statistischen, auf maschinellem Lernen basierenden Verfahren setzen wir auch umfangreiche semi-automatisch erstellte, linguistische Module ein, die dann durch systematische Evaluierung auf Korpora schnell ergänzt und verbessert werden können. Basierend auf unseren Extraktionsmethoden ist es nun möglich, im Bereich der semantischen Suche deutliche Fortschritte zu machen. Insbesondere Personensuchmaschinen können sich unsere detaillierten Analysemethoden zu Nutze machen, um beispielsweise zu ermitteln, wer in welcher Funktion bei welcher Firma von wann bis wann beschäftigt war.
Keywords: Natural Language Processing

Reverse Engineering with the Reclipse Tool Suite - von Detten, Markus; Meyer, Matthias; Travkin, Dietrich (Proceedings of the 32nd ACM/IEEE International Conference on Software Engineering (ICSE 2010), Cape Town, South Africa, May 2-8, 2010)

Reclipse - A Reverse Engineering Tool Suite - von Detten, Markus; Meyer, Matthias; Travkin, Dietrich
Design pattern detection is a reverse engineering methodology that helps software engineers to analyze and understand legacy software by recovering design decisions and thereby providing deeper insight into software. In this report we present Reclipse, a reverse engineering tool suite based on Fujaba. Reclipse provides static and dynamic design pattern detection in combination with a pattern rating that is used to evaluate the quality of our detection results.

Formal Scenario-based Requirements Specification and Test Case Generation in Healthcare Applications - Löffler, Renate; Meyer, Matthias; Gottschalk, Matthias (Proceedings of the 2010 ICSE Workshop on Software Engineering in Health Care)

Kompass Recht: Darstellung des gesamten Deutschen Rechts in 30 Einzelbänden mit anliegender CD

Designing Self-healing in Automotive Systems - Seebach, Hella; Nafz, Florian; Holtmann, Jörg; Meyer, Jan; Tichy, Matthias; Reif, Wolfgang; Schäfer, Wilhelm (Lecture Notes in Computer Science)
Self-healing promises to improve the dependability of systems. In particular safety-critical systems like automotive systems are well suited application, since safe operation is required in these systems even in case of failures. Prerequisite for the improved dependability is the correct realization of the self-healing techniques. Consequently, self-healing activities should be rigorously specified and appropriately integrated with the rest of the system. In this paper, we present an approach for designing self-healing mechanisms in automotive systems. The approach contains a construction model which consist of a structural description as well as an extensive set of constraints. The constraints specify a correct system structure and are also used in the self-healing activities. We exemplify the self-healing approach using the adaptive cruise control system of modern cars.

Mit Satzmustern von textuellen Anforderungen zu Modellen - Holtmann, Jörg (OBJEKTspektrum)
Im Bereich der eingebetteten Systeme, beispielsweise im Automobilsektor, wird heutzutage immer mehr auf eine modellbasierte Entwicklung gesetzt. Die Anforderungen an die zu entwickelnden Systeme werden dagegen aus juristischen Gründen und zwecks einer guten Verständlichkeit nach wie vor rein textuell formuliert. Ein Prosatext lässt sich allerdings wegen der Fülle von Formulierungsmöglichkeiten nicht automatisiert verarbeiten. Dies führt dazu, dass die Qualitätsanalyse der Anforderungen und der Übergang von textuellen Anforderungen zu Systemmodellen auf manuelle Weise erfolgen müssen. Dies kostet Zeit und ist fehleranfällig. In diesem Beitrag wird ein Ansatz vorgestellt, mit dem Anforderungen auf Basis von Satzmustern weiterhin textuell, aber gleichzeitig auch automatisiert verarbeitbar formuliert werden können.

Eine erweiterte Systemmodellierung zur Entwicklung von softwareintensiven Anwendungen in der Automobilindustrie - Meyer, Jan; Holtmann, Jörg; Schäfer, Wilhelm; Nickel, Ulrich A. (Software Engineering 2010 – Workshopband (inkl. Doktorandensymposium))
Heutige Transportsysteme, wie z.B. Automobile sind gekennzeichnet durch eine Vielzahl von Funktionalitaet, die sehr haeufig durch Software realisiert wird. Hiermit ist eine Zunahme der Komplexitaet festzustellen. Zur Beherrschung dieser Komplexitaet und damit einhergehend die Aufteilung des Systems in verschiedene Komponenten, ist eine Gesamtmodellierung des Systems inklusive des Verhaltens unerlaesslich. Ein besonderer Augenmerk liegt auf Grund der Echtzeitsysteme in dieser Domaene dabei auf der Modellierung von Zeiten auf Systemebene. Die derzeitigen Modellierungskonzepte, wie beispielsweise die Systems Modeling Language (SysML), sind dafuer aber noch nicht ausreichend. In dem hier vorgestellten Ansatz wird eine erweiterte Systemmodellierung vorgestellt, die zusaetzlich eine formale Spezifizierung von Zeiten erlaubt. Durch diese Modellierung sind weitere Analysemethoden, wie z.B. Simulationen oder Verifikationen moeglich, die zum einen die sicherheitsrelevante Funktionalitaet sicherstellen und zum anderen die Qualitaet der Software steigern.

Bridging visible and telecom wavelengths with a single-mode broadband photon pair source - Söller, C.; Brecht, Benjamin; Mosley, P. J.; Zang, L. Y.; Podlipensky, A.; Joly, N. Y.; Russell, P. St. J.; Silberhorn, Christine (Physical Review A)

Transformational Plasmon Optics - Liu, Yongmin; Zentgraf, Thomas; Bartal, Guy; Zhang, Xiang (Nano Letters)

Light-driven nanoscale plasmonic motors - Liu, Ming; Zentgraf, Thomas; Liu, Yongmin; Bartal, Guy; Zhang, Xiang (Nature Nanotechnology)

An Optical “Janus” Device for Integrated Photonics - Zentgraf, Thomas; Valentine, Jason; Tapia, Nicholas; Li, Jensen; Zhang, Xiang (Advanced Materials)

All-Liquid Photonic Microcavity Stabilized by Quantum Dots - Yim, Tae-Jin; Zentgraf, Thomas; Min, Bumki; Zhang, Xiang (Journal of the American Chemical Society)

Far-field measurement of ultra-small plasmonic mode volume - Zhang, Shuang; Park, Yong-Shik; Liu, Yongmin; Zentgraf, Thomas; Zhang, Xiang (Optics Express)

Automated 3D-motion planning for ramps and stairs in intra-logistics material flow simulations - Fischer, Matthias; Renken, Hendrik; Laroque, Christoph; Schaumann, Guido; Dangelmaier, Wilhelm (Proceedings of the 2010 Winter Simulation Conference)
Commercial software of material flow simulations has the ability to layout the simulated models. Arranged equipment, such as conveyors or machines, includes the need to model and determine motion paths for moving objects like forklifts or automatically guided vehicles, so that the simulation framework is able to navigate all vehicles across those motion paths. After analyzing first scenarios, the user often carries out layout changes in the simulation model, e.g. moving, adding or deleting equipment. However, those changes cause time consuming, additional modeling of the motion paths for the user. Our motion planning algorithm reduces these changes by automatically determining the motion paths for moving objects, depending on an actual model layout without colliding with other objects. The algorithm works on the basis of the virtual scenes 3D-data used for the simulation models visualization. We demonstrate the technique with a multi-floor building example.

A Large-Scale Distributed Environment for Peer-to-Peer Services - Gehweiler, Joachim; Meyer auf der Heide, Friedhelm; Schroeder, Ulf-Peter

Adapting a sensor net to the dynamic environment in a wildlife scenario - a case study - Blesa, Maria J.; Blum, Christian; de Caro, Angelo; Degener, Bastian; Kempkes, Barbara; Leone, Piere; Persiano, Giuseppe; Meyer auf der Heide, Friedhelm; Mylonas, Georgios

Building short chains of mobile robots locally with a bounded stepwidth - Brandes, Philipp; Degener, Bastian; Kempkes, Barbara; Meyer auf der Heide, Friedhelm
We are given a winding chain of $n$ mobile robots between two stations in the plane, each of them having a limited viewing range. It is only guaranteed that each robot can see its two neighbors in the chain. We analyze a simple and natural parallel strategy to shorten the chain in a time model where each relay is allowed to move up to a distance of $δ$ in each time step. This model fills the gap between the previously used discrete time model and the continuous time model which was introduced recently in \cite{sirocco}. We analyze the strategy with respect to two quality measures: the number of time steps and the maximum distance to be traveled by the robots, which are the major energy consumers in this scenario. We provide asymptotically tight or almost tight bounds in this time model for both quality measures and it turns out that the best choice for $δ$ is $δ \in Θ(\frac{1}{n})$, since this minimizes the number of time steps as well as the maximum traveled distance.

Editorial - Peckhaus, Volker (History and Philosophy of Logic)

Bandwidth allocation in cellular networks with multiple interferences - Bar-Yehuda, Reuven; Polevoy, Gleb; Rawitz, Dror (DIALM-PODC)

Beiträge der Sektion I "'Spoken' English through the Centuries." Sprachwissenschaftliche Sektion beim Anglistentag 2009 in Klagenfurt. - Claridge, Claudia; Mindt, Ilka (Anglistentag 2009 Klagenfurt. Proceedings)

intentio - Peckhaus, Volker; Gethmann, Carl Friedrich (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 4: Ins–Loc)

Lévinas, Emmanuel - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 4: Ins–Loc)

Spoken English through the centuries: Introduction - Claridge, Claudia; Mindt, Ilka (Anglistentag 2009 Klagenfurt. Proceedings)

Methoden der Korpuslinguistik: Der korpus-basierte und der korpus-geleitete Ansatz - Mindt, Ilka (Kompendium Korpuslinguistik. Eine Bestandsaufnahme aus deutsch-tschechischer Perspektive)

Hormone-based Control for Multi-modular Robotics - Hamann, Heiko; Schmickl, Thomas; Stradner, Jürgen; Crailsheim, Karl; Levi, Paul; Kernbach, Serge (Symbiotic Multi-Robot Organisms: Reliability, Adaptability, Evolution)

Page migration in dynamic networks - Bienkowski, Marcin

Collective graph exploration - Dynia, Miroslaw

Kinetic Facility Location - Degener, Bastian; Gehweiler, Joachim; Lammersen, Christiane (Algorithmica)

Literaturwissenschaft - Eke, Norbert Otto; Allkemper, Alo
4. Auflage 2014

A distributed diffusive heuristic for clustering a virtual P2P supercomputer - Gehweiler, Joachim; Meyerhenke, Henning (Proceeedings of 24th International Parallel and Distributed Processing Symposium (IPDPS, HPGC))

On Dynamic Graph Partitioning and Graph Clustering using Diffusion - Gehweiler, Joachim; Meyerhenke, Henning (Dagstuhl Seminar Proceedings 10261: Algorithm Engineering)
Load balancing is an important requirement for the efficient execu-tion of parallel numerical simulations. In particular when the simulation domainchanges over time, the mapping of computational tasks to processors needs tobe modified accordingly. State-of-the-art libraries for this problem are basedon graph repartitioning. They have a number of drawbacks, including the opti-mized metric and the difficulty of parallelizing the popular repartitioning heuris-tic Kernighan-Lin (KL).Here we further explore the very promising diffusion-based graph partitioningalgorithm DIBAP (Meyerhenke et al., JPDC 69(9):750–761, 2009) by adaptingDIBAP to the related problem of load balancing. Experiments with graph se-quences that imitate adaptive numerical simulations demonstrate the applicabilityand high quality of DIBAP for load balancing by repartitioning. Compared to thefaster state-of-the-art repartitioners PARMETIS and parallel JOSTLE, DIBAP’ssolutions have partitions with significantly fewer external edges and boundarynodes and the resulting average migration volume in the important maximumnorm is also the best in most cases.We also prove that one of DIBAP’s key components optimizes a relaxed versionof the minimum edge cut problem. Moreover, we hint at a distributed algorithmbased on ideas used in DIBAP for clustering a virtual P2P supercomputer.

Thread Migration and Checkpointing in Java - Thies, Michael; Gehweiler, Joachim

Adaptive Action Selection Mechanisms for Evolutionary Multimodular Robotics - Kernbach, Serge; Schmickl, Thomas; Hamann, Heiko; Stradner, Jürgen; Schlachter, Florian; Schwarzer, Christopher s. F.; Winfield, Alan F. T.; Matthias, Rene (Artificial Life XII (ALife XII))

Rekonstruktionen von Kontinuität zwischen 1600 und 1800: Überbrückung der durch Politik, Religion und Krieg verursachten Zäsuren - Seng, Eva- Maria (Geschichte der Rekonstruktion. Konstruktion der Geschichte. Publikation und Ausstellungskatalog, Pinakothek der Moderne)

Improved Hardness of Approximation for Stackelberg Shortest-Path Pricing - Briest, Patrick; Chalermsook, Parinya; Khanna, Sanjeev; Laekhanukit, Bundit; Nanongkai, Danupon (Workshop on Internet and Network Economics (WINE))

Algorithmische Grundlagen verteilter Speichersysteme - Meyer auf der Heide, Friedhelm; Scheideler, Christian (Informatik Spektrum)

Stadtbaukunst - Seng, Eva- Maria (Enzyklopädie der Neuzeit, Stuttgart)

Pricing Randomized Allocations - Briest, Patrick; Chawla, Shuchi; Kleinberg, Robert; Weinberg, S. Matthew (Proceedings of the Twenty-First Annual ACM-SIAM Symposium on Discrete Algorithms)

Foreword - Gavoille, Cyril; Patt-Shamir, Boaz; Scheideler, Christian (Theory of Computing Systems)

Peer-to-peer networks based on random graphs - Mahlmann, Peter

Local, distributed approximation algorithms for geometric assignment problems - Degener, Bastian